Clinical researchThe training needs of doctors working in England and in Poland with breastfeeding women - Kosmala-Anderson, Joanna; Wallace, Louise M.; Dunn, Orla; Law, Susan (Archives of Medical Science, 2007)
Introduction: The aim of this study was to compare the training needs of Polish and English medical practitioners in breastfeeding support skills. Self-assessed competence in 22 skill areas, perceived need for update of breastfeeding support skills and perception of organizational barriers for breastfeeding were compared. Material and methods: Surveys in both countries were conducted using largely similar questionnaires and procedures. The English sample (n=177) consisted of paediatricians and GPs; the Polish sample (n=54) included neonatologists, obstetricians, paediatricians and GPs. Results: There were no differences in clinical practice competence level of the two samples; Polish doctors assessed themselves as more competent in regard to educative skills. Both English and Polish practitioners would welcome update of breastfeeding skills, but this need was expressed more frequently by Polish doctors. In both Poland and England greater intensity of breastfeeding experience was associated with identifying more areas for future update. However, unlike the English sample, within the Polish sample, doctors who were less competent expressed greater need for update. In both samples, greater breastfeeding knowledge was associated with higher self-assessed competence level. English doctors experienced more organizational barriers. Both Polish and English practitioners indicated early hospital discharge as one of the biggest barriers for breastfeeding support. Conclusions: We conclude that core training is recommended to all practitioners in both countries, and that reliance on self assessed competence and need for update are not useful indicators for the deployment of scarce training resources.